A New Model of Femininity: Marguerite Coppin, Decadent Fiction and Belgian Girls' Education. (2nd April 2016) - Larson, Sharon
Abstract : Published in 1889 and set in fin-de-siècle Brussels, Marguerite Coppin's Ressort cassé is the story of a cultivated, well-educated young woman and her eventual social exclusion. After attending an innovative secular school visibly modelled after Isabelle Gatti de Gamond's 'Cours d'Éducation pour jeunes filles, ' protagonist Renée Michelli is unable to find her place in the gendered spheres of society. Her subsequent lifestyle of sexual predation and aggression recalls characteristics typical of the Decadent femme fatale . However, with its attention to girls' education reform and female intellectual subjectivity, Coppin's novel rewrites and parodies Decadent anxieties about malevolent femininity and the female mind. Through an emphasis on Renée's critical capacities as a reader and satirical intertextual references to the pathologized figure of the woman reader, the text raises questions about Gatti's programme, pedagogical philosophy and the place for women's intellect in both society and Decadent fiction.